DETERMINATION OF TRANSPORT PARAMETERS FOR SOLUTES IN SALT-TREATED SOIL COLUMNS - & Naser, Bahia (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A laboratory experiment was carried out at the Department of Soil Sciences and Water Resources, College of Agriculture, University of Baghdad. Silty clay soil was treated with three salt solutions (NaCl, CaCl2 and mixed NaCl–CaCl2). Homogeneously packed soil columns (10 cm, 40 cm) were leached six times using tap water. Effluent samples were collected to determine ion concentration Cl-, Ca++, Na+, K+ and Mg++. Breakthrough curves were used to estimate solute transport parameters (retardation factor, peclet number) using an analytical solution of convection-dispersion equation (CDE) by CXTFIT program. The results showed that relative concentration of chloride was increased rapidly with calcium chloride, which increased sodium leaching rate at starting of breakthrough curve. Sodium chloride increased water requirements for calcium displacement. Results indicated a good fitting of convection-dispersion equation with breakthrough curves data. The best-fit were used to calculate peclet number, retardation factor and dispersion coefficient. When soil was treated with calcium chloride, Peclet number of chloride was increased from 3.13 to 6.48, while it has been decreased for calcium, sodium and potassium. Sodium chloride decreased peclet numbers of chloride, calcium and sodium. Also mixed salts increased sodium peclet number from 1.01 to 9.02. Results showed, calcium chloride decreased retardation factor of chloride from 1.59 to 0.50, while it has been increased from 1.39, 1.58 to 175.00, 493.36 for each of sodium and potassium, respectively. Retardation factor of calcium was decreased when soil was treated with sodium chloride or mixed salts. Dispersion coefficient was decreased for chloride, and increased for calcium and magnesium. When soil was treated with calcium chloride, dispersion coefficients have been increased from 24.29, 25.56 to 40.51, 40.89 cm2hr-1 for sodium and potassium, respectively.